2019
DOI: 10.1123/japa.2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin Ingestion Before Nocturnal Sleep on Postural Balance and Subjective Sleep Quality in Older Adults

Abstract: The present study aimed to investigate the effect of acute nocturnal melatonin (MEL) ingestion on sleep quality, cognitive performance and postural balance in older adults. Twelve older men (58± 5.74 years) volunteered to participate in this study. The experimental protocol consisted in two testing sessions after nocturnal MEL (10 mg) or placebo (PLA) ingestion the night before the tests. During each session, sleep quality tests, cognitive tests and postural balance protocol were conducted. Static and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In this study, the EX-MEL group showed a greater improvement of postural balance and QoL than the EX-PLA group, suggesting a positive effect of MEL supplementation when combined with intradialytic exercise in HD patients. Similarly, previous study showed an improvement of postural balance in dual-task after acute MEL ingestion in elderly patients [14]. Moreover, 12 months of MEL supplementation with the same dose used in this study (3 mg) improved QoL in HD patients [15].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, the EX-MEL group showed a greater improvement of postural balance and QoL than the EX-PLA group, suggesting a positive effect of MEL supplementation when combined with intradialytic exercise in HD patients. Similarly, previous study showed an improvement of postural balance in dual-task after acute MEL ingestion in elderly patients [14]. Moreover, 12 months of MEL supplementation with the same dose used in this study (3 mg) improved QoL in HD patients [15].…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the dual‐task condition, postural balance improved only in EX‐MEL compared with EX‐PLA and C‐PLA. Similarly, Kamoun et al [14] showed an improvement of static postural balance in dual‐task with a single dose of MEL (10 mg) ingested before nocturnal sleep in older adults. Shin et al [41] showed that these frail patients have poorer postural balance than age‐matched healthy subjects in particular while quiet standing with a cognitive task.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Reduced heart rate and better physiological responses also lead to visual acuity, sensory mechanisms, atrial system, postural control, and balance. Research has also shown that the negative effects of sleep deprivation on postural control would be due to reduced visual input, atrial system function, and impaired musculoskeletal function (17). Research has shown that partial sleep deprivation increases reaction time and decreases selective and continuous attention (1).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in central and peripheral orexins have been linked to narcolepsy, anorexia, age-related cognitive decline and neurodegenerative diseases. Orexin receptor antagonists can promote sleep signals during the night and orexin therapies can increase sleep and memory as well as cognition [65][66][67].…”
Section: Potential Underlying Mechanisms For Sleep Problems In the Agingmentioning
confidence: 99%